Implementation of the hybrid course on basic wheelchair service provision for Colombian wheelchair service providers - Burrola-Mendez, Yohali (PLoS One, 2018)
INTRODUCTION: People with mobility impairments often rely on wheelchairs as their primary means of mobility. Untrained wheelchair service providers may provide inappropriate wheelchairs and services which result in negative consequences in wheelchair users’ health, quality of life, safety, and social participation. This study aimed to evaluate the influence of the Spanish Hybrid Course on Basic Wheelchair Service Provision, a training based on the World Health Organization’s Wheelchair Service Training Program-Basic Level, to increase knowledge in basic level wheelchair service provision among a group of wheelchair service providers from Colombia. In addition, we developed a satisfaction survey which participants completed after the training to understand levels of satisfaction with the training intervention. METHODS: A quasi-experimental study was conducted to evaluate changes in basic level wheelchair knowledge using the Wheelchair Service Provision–Basic Test. Paired sample t tests were used to assess pre-and post-training changes in basic level wheelchair knowledge. The Hybrid Satisfaction Survey was developed in collaboration with a multidisciplinary, international stakeholders’ group. The survey’s construct of interest was level of satisfaction determined by interaction, instructor, instruction methodology, content, and technology, using a five-point Likert scale (0 = strongly disagree to 4 = strongly agree). The survey was completed anonymously after the training intervention and analyzed using frequencies and percentages. RESULTS: Fifteen wheelchair service providers in Colombia completed the Spanish Hybrid Course. Mean post-scores were significantly higher (Mean (M) = 56.13, Standard Deviation (SD) = 7.8), than pre-assessment scores (M = 50.07, SD = 8.38, t(14) = 4.923, p = <0.0001). Participants who completed the surveys (N = 15) reported that the Spanish Hybrid Course was well received, with 98.66% of responses distributed in favorable levels (>3). CONCLUSIONS: The Spanish Hybrid Course proved to be effective in increasing basic level wheelchair knowledge with a high satisfaction level among participants. Further testing is needed to evaluate the effectiveness of this course across different individuals and countries as a potential tool to build professional capacity in basic level wheelchair provision.